Answer: 25x² - 64
<u>Step-by-step explanation:</u>
(5x + 8)(5x - 8)
= 5x(5x - 8) + 8(5x - 8)
= 25x² - 40x + 40x - 64
= 25x² + 0x - 64
= ![\large\boxed{25x^2-64}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B25x%5E2-64%7D)
NOTE: descending powers means the biggest exponent goes first, then the next biggest exponent, etc.
For example: x⁴ then x³ then x² then x then the number (which is actually x⁰)
Answer:
- y= 7
- y= -3
- y= -4
- y= -8
Step-by-step explanation:
y= -5x+1
=-5.-1+1
=7
Now you can do this method
Answer:
bodmas
Step-by-step explanation:
enables to go step by step
Answer:
Step-by-step explanation:
Use the formula
![A(t)=P(1+\frac{r}{n})^{nt}](https://tex.z-dn.net/?f=A%28t%29%3DP%281%2B%5Cfrac%7Br%7D%7Bn%7D%29%5E%7Bnt%7D)
Fill in the info we are given:
and
and
1210 = P(1.255632915) so
P = $964
Triangular prism. It has three sides so a triangle